2009
DOI: 10.1080/09593330902984751
|View full text |Cite
|
Sign up to set email alerts
|

Investigating different mechanisms for biogenic selenite transformations:Geobacter sulfurreducens,Shewanella oneidensisandVeillonella atypica

Abstract: The metal-reducing bacteria Geobacter sulfurreducens, Shewanella oneidensis and Veillonella atypica, use different mechanisms to transform toxic, bioavailable sodium selenite to less toxic, non-mobile elemental selenium and then to selenide in anaerobic environments, offering the potential for in situ and ex situ bioremediation of contaminated soils, sediments, industrial effluents, and agricultural drainage waters. The products of these reductive transformations depend on both the organism involved and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 51 publications
2
67
0
Order By: Relevance
“…Elemental Se is produced as spherical particles in the nanometer size range, localized either inside or outside the cell. Recent research showed that nanoscale semiconductor materials (also called quantum dots) can be synthesized by using microbial metabolism (53,54,66). Selenium-respiring microorganisms are used to reduce selenium oxyanions to produce selenide, which combines with metal cations (i.e., Cd and Zn) and forms metal selenide (i.e., CdSe and ZnSe) quantum dots.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elemental Se is produced as spherical particles in the nanometer size range, localized either inside or outside the cell. Recent research showed that nanoscale semiconductor materials (also called quantum dots) can be synthesized by using microbial metabolism (53,54,66). Selenium-respiring microorganisms are used to reduce selenium oxyanions to produce selenide, which combines with metal cations (i.e., Cd and Zn) and forms metal selenide (i.e., CdSe and ZnSe) quantum dots.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial methylation of selenium forms volatile compounds, such as dimethyl selenide, dimethyl diselenide, dimethyl selenyl sulfide, hydrogen selenide, and methaneselenol (53,57). Microbial selenium methylation is significant in environmental settings, although it is a slow process (54). For additional details, the reader is referred to excellent reviews on microbial methylation of metalloids (58,59).…”
Section: Se 0 -Respiring Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…However, they become immobilized when the selenate and selenite are microbially reduced to Se 0 (20). Microbial reduction of Se 0 to selenide (Se 2Ϫ ) has received limited attention, but it is noteworthy that insoluble Se 0 can be reduced microbiologically to soluble selenide (21,22).…”
Section: ϫmentioning
confidence: 99%
“…Heating was avoided as amorphous Se(0) undergoes a glass transition at temperatures above 30-35 C (Pearce et al, 2009). …”
Section: Chemicalsmentioning
confidence: 99%